Can we use the Flipped Classroom Model to teach Black-box Testing to Computer Students? - Paschoal, Leo Natan; Oliveira, Brauner R. N.; Nakagawa, Elisa Yumi; Souza, Simone R. S. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
Computer science programs have been delivering newly undergraduate students to the software industry without sufficient knowledge on how to perform software testing activities. It occurs because that activity is usually taught as part of Software Engineering courses, which means that teachers have to put a lot of efforts to teach the main testing techniques and criteria along with many other contents. In this way, the content is mostly addressed in a theoretical way as the teacher has to stick to the course schedule and has no time to address the testing practice. On the other hand, some studies reported the efforts of professors to optimize the time during classes and attract students to the software testing area. These efforts are associated with the employment of activities in which students are actively engaged in the classroom, solving problems, developing real projects, or dealing with real cases. A pedagogical model that seeks to leverage such an approach is the flipped classroom model. However, while some have praised that model, others have criticized it. In the state of the art, there is no consensus about the appropriateness of flipped classroom for specific learning contents. In this paper, we present an experimental study that was conducted to verify the suitability of the flipped classroom model to teach software testing, especially black-box testing. This study comprised an analysis of students' learning gains when subject to the flipped model and the workload introduced when compared to the traditional teaching model.